Genetic Diversity of Mycobacterium tuberculosis from Guadalajara, Mexico and Identification of a Rare Multidrug Resistant Beijing Genotype - Flores Treviño, Samantha Maribel; Morfín Otero, Rayo; Rodríguez Noriega, Eduardo; Gonzalez Diaz, Esteban E.; Pérez Gómez, Héctor Raúl; Bocanegra García, Virgilio; Vera Cabrera, Lucio; Garza González, Elvira (Public Library of Science, 2015)
Determining the genetic diversity of M. tuberculosis strains allows identification of the distinct Mycobacterium tuberculosis genotypes responsible for tuberculosis in different regions. Several studies have reported the genetic diversity of M. tuberculosis strains in Mexico, but little information is available from the state of Jalisco. Therefore, the aim of this study was to determine the genetic diversity of Mycobacterium tuberculosis clinical isolates from Western Mexico. Sixty-eight M. tuberculosis isolates were tested for susceptibility to first-line drugs using manual Mycobacteria Growth Indicator Tube method and genotyped using spoligotyping and IS6110-restriction fragment length polymorphism (RFLP) pattern analyses. Forty-seven (69.1%) isolates were grouped into 10 clusters and 21 isolates displayed single patterns by spoligotyping. Three of the 21 single patterns corresponded to orphan patterns in the SITVITWEB database, and 1 new type that contained 2 isolates was created. The most prevalent lineages were T (38.2%), Haarlem (17.7%), LAM (17.7%), X (7.4%), S (5.9%), EAI (1.5%) and Beijing (1.5%). Six (12.8%) of the clustered isolates were MDR, and type 406 of the Beijing family was among the MDR isolates. Seventeen (26.2%) isolates were grouped into 8 clusters and 48 isolates displayed single patterns by IS6110-RFLP. Combination of IS6110-RFLP and spoligotyping reduced the clustering rate to 20.0%. The results show that T, Haarlem, and LAM are predominant lineages among clinical isolates of M. tuberculosis in Guadalajara, Mexico. Clustering rates indicated low transmission of MDR strains. We detected a rare Beijing genotype, SIT406, which was a highly resistant strain. This is the first report of this Beijing genotype in Latin America.